2021
DOI: 10.53730/ijhs.v5n3.1458
|View full text |Cite
|
Sign up to set email alerts
|

“Clinical masks” of congenital malformations of urinary system in children of early age

Abstract: Nowadays there is an increase in nephropathy in young children, which is associated not only with environmental impacts, but also with an increase in the incidence of congenital and hereditary caused forms of diseases, an increase in the incidence of mothers, and an improvement in diagnosis. In order to analyze the frequency of congenital malformations of the urinary system in young children under the “clinical masks” of various somatic pathologies, 864 cards of inpatients that were treated in the Early Childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…After analysing data on daytime and nighttime urination at 3-, 6-, and 12-months post-surgery, researchers found that urinary retention improved significantly. Notably, this improvement was more pronounced in younger patients (29,30).…”
Section: Miki Et Al (mentioning
confidence: 85%
“…After analysing data on daytime and nighttime urination at 3-, 6-, and 12-months post-surgery, researchers found that urinary retention improved significantly. Notably, this improvement was more pronounced in younger patients (29,30).…”
Section: Miki Et Al (mentioning
confidence: 85%
“…All other countries lag two orders of magnitude behind developed countries in efforts to fight for newborn life. Japan bears the greatest cost of medical struggle in the lives of infants (Lukyanenko et al, 2021). The only country that has survived two nuclear military disruptions and one peaceful one at a nuclear power plant has understood the value of the real cost of medical treatment, including infants, which is why the Japanese have the highest life expectancy at 84 years.…”
Section: Resultsmentioning
confidence: 99%
“…Its need should be discussed individually for each patient if signs of cystocele are seen at Va +2.0 on Valsalva testing. A potential disadvantage of this technique is the lack of effectiveness and the risk of recurrence of prolapse in the posterior segment of the vagina in case of hidden defects in the facial structures and the formation of de novo GP signs in this segment (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%